Life Esidimeni: Portraits of Lives Lost - Levy, Moira (New Agenda: SA Journal of Social and Economic Policy, 2024)
It’s hard going, but readers of Life Esidimeni: Portraits of Lives Lost must keep going to the very last page of this book because it is our responsibility as citizens to make sure this tragedy never happens again and that those in positions of authority who abuse their power are called to account. “That is what the inquest has been about – justice through accountability,” Adila Hassim, lead counsel in the Life Esidimeni arbitration and inquest, writes in the closing essay. Hassim reminds us that the Life Esidimeni tragedy would have been avoided if those in charge did what they were supposed to do.